The Influence of Product Quality and Price Discount on Purchasing Decisions (A Survey on consumers at Wendy’s Transmart in the city Tasikmalaya) - Gilang Syefa Lugina; Depy Muhamad Pauzy; Kusuma Agdhi Rahwana (Penerbit Jurnal Indonesia, 2022)
This study aims to determine the effect of product quality and price discounts on purchasing decisions (Survey of consumers at Wendy's Transmart Tasikmalaya). This study uses a survey method. The type of data used is primary data and secondary data, with a research sample of 100 respondents from consumers and using the accidental sampling method. The analytical tool used in SPSS version 25. Data collection techniques used interviews, questionnaires and documentation studies. The results showed that product quality and price discounts simultaneously had a significant effect on purchasing decisions. Product quality partially has a significant effect on purchasing decisions. Discounts partially have a significant effect on Purchase Decisions.